Acute Bilateral Retrobulbar Optic Neuritis Revealing Sphenoethmoidal Sinus Neuroendocrine Carcinoma - Belfaiza Soukaina; Marion Chatain; Benjelloul Fatiha (Indian Journal of Medical Specialities)
Primary sinonasal neuroendocrine carcinoma is a rare tumor of extreme malignancy. The diagnosis is often made at an advanced stage. The most recently documented treatment for nonmetastatic paranasal sinus neuroendocrine carcinoma consists of chemotherapy (cisplatin-VP16) followed by radiotherapy. Surgery is reserved for resectable tumors that do not respond well to chemotherapy. We report the case of a patient admitted for acute bilateral Retrobulbular optic neuropathy (RBON) revealing a sphenoethmoidal sinus neuroendocrine carcinoma.